Program Pengabdian Kepada Masyarakat Berbasis Blended Untuk Pembangunan Pariwisata Berkelanjutan - Gita Putri, Octaviani (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
The most important objective of implementing community service (PKM) is to emphasize the focus on efforts to measure the level of community participation in the development of sustainable rural tourism. It involves collaboration between educational institutions and the communities they serve. However, most of the community service carried out by lecturers is carried out independently, and a small portion is supported financially by the relevant universities. Apart from that, there are still many tourist villages that have a lot of tourism potential but have not received adequate assistance because they have many limitations such as limited road access, access distance, limited costs and so on. This condition is a challenge for universities in Indonesia in improving the quality of community service programs. This research aims to provide recommendations for optimizing PKM with a mix of offline and online or also called blended-based PKM, so that it is hoped that it can maximize assistance to tourist villages in sustainable tourism development. This research uses a descriptive research method with a qualitative approach with a systematic literature review method, observation and SWOT analysis of both types of programs and provides alternative solutions based on the results of the analysis. The data source used is secondary data, which comes from journal articles and other reference sources that are relevant to the topic of discussion. Based on the research results, it was found that implementing online PKM can help answer offline PKM problems but in reality it is not yet effective, so there is a need for a mix of online and offline PKM, namely blended-based PKM so that PKM becomes more effective. Apart from that, blended-based PKM will have an indirect impact in accordance with UNWTO's Sustainable Development Goals, namely number four, Quality Education and number eight, namely Decent Work and Economic Growth. So, with the development of this blended-based PKM program, it is hoped that it can increase sustainable tourism development through improving the quality of education in assisting tourist villages as well as increasing decent work and economic growth in tourist villages.